The Impact of Shared Governance Model's Implementation on Professional Governance Perceptions of Nurses in Saudi Arabia: A Randomised Controlled Trial - Hamdan M.; Jaafar A.H. (Wiley-Hindawi, 2025)
Objective. This study aimed to evaluate the impact of the shared governance model application on the level of perceived professional governance among clinical nurses in a tertiary hospital in Riyadh. Background. Professional governance continues traditional governance, shared governance, and self-governance. Shared governance (SG) is the engagement of clinical nurses in decision-making at different levels. This empowers nurses, increases job satisfaction, improves clinical outcomes, and enhances patient satisfaction. Methods. This randomised control trial in which researchers distributed the Index of Professional Nursing Governance (IPNG) to a random sample of 440 nurses working in a 1200-bed tertiary hospital in Riyadh and divided into experimental and control groups. The intervention included designing and implementing a nursing shared governance model at the hospital level; professional governance was measured before and eight months after implementation. The IPNG was used to measure nurses' perceived level of professional governance before and after the intervention. The sample was divided into experimental and control groups. Results. By comparing experimental and control groups, there was no statistically significant difference between them regarding professional governance subscales and the total IPNG scores before the intervention. At the same time, there was a considerable difference between them after the intervention. Moreover, the scores of the six professional governance subscales and the overall IPNG scores significantly increased after the intervention in the experimental group. They showed no significant difference in the control group. Conclusion. Designing and implementing specific shared governance structures and processes effectively enhanced nurses' perceived level of shared governance at the hospital, as evidenced by significantly higher postintervention IPNG scores. Elements of the shared governance model that proved effective included engaging nurses in decision-making at various organizational levels and empowering their involvement. ? 2024 Mahmoud Hamdan and Amar Hisham Jaafar.